Migration and collective action in the commons: application of social-ecological system framework with evidence from China - Yahua Wang; Yiqing Su; Eduardo K. Araral (Ecology and Society, 2022)
Much is known about collective action in the commons but little is known about the effects of migration as an exogenous shock. We study the case of China where at least 280 million people have migrated from the rural areas to the cities over the last four decades. We apply the social-ecological system (SES) framework along with the theory of collective action using survey data from 1985 households in 20 provinces throughout China. Data was analyzed using confirmatory factor analysis, ordered probit regression with instrumental variables, structural equation modeling, and interaction effects analysis. We find that migration exerts a significant negative effect on collective action in the commons and its effect is mediated by four mechanisms: resource dependence, leadership, social capital, and sense of community. Of these, resource dependence and leadership account for about two-thirds of the total effect. The SES framework has been shown to be a useful tool for empirically studying complex, multi-variable, nonlinear, cross-scale, and dynamic social-ecological systems.